2011
DOI: 10.1186/1471-2474-12-131
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover in passive smoking female rat: relationships to change in bone mineral density

Abstract: BackgroundMany studies have identified smoking as a risk factor for osteoporosis, but it is unclear whether passive smoking has an effect on bone mineral density and bone turnover and if such an effect could cause osteoporosis.The purpose of the study was to investigate the effect of passive smoking on bone mineral density (BMD) and bone turnover and the relationship between BMD and bone turnover in female rat.MethodsForty-eight female Wistar rats were randomized into six groups: 2-month, 3-month,4-month smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…Similar to the findings of Gao et al 15 and Ino et al 16 , in this study we also observed that the groups exposed to cigarette smoke continued to show lesser measurements in comparison with the control group. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to the findings of Gao et al 15 and Ino et al 16 , in this study we also observed that the groups exposed to cigarette smoke continued to show lesser measurements in comparison with the control group. …”
Section: Discussionsupporting
confidence: 92%
“…The study by Gao et al 15 found a statistically significant difference only after 4 months of exposure; the rats which were exposed for 2 or 3 months did not exhibit differences in the bone parameters studied 4 …”
Section: Discussionmentioning
confidence: 91%
“…Fung et al [28] reported that a 2-month period of nicotine application does not change BMC and BMD values. Gao et al [29] reported that 2-or 3-month periods of nicotine application did not change BMD values, but a 4-month period of application reduced BMD values. The controversial results were likely due to the variable dosages and methods of nicotine administration and the different healing models used to study the influence of nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the methods are outdated and some currently in use have been modified for automated testing, but all are old and do not reflect the best available techniques. In fact, given the importance of acid phosphatase to the conclusions of the paper, it is surprising that the authors did not use a current and commercially available rat‐specific immunoactivity assay for the TRAP isoform 5b that is specific for changes in bone metabolism, as was done in another recent paper (Gao et al ., ). Instead, an older colorimetric method for TRAP was used that is not specific for bone.…”
Section: Analytical Problemsmentioning
confidence: 97%
“…Reporting such information for critical analyses is not rare or unusual. Precision and accuracy data were recently reported for both bone‐specific ALP and bone‐specific TRAP assays by other authors investigating alterations in bone metabolism in the rat, even though they were using validated commercial kits for both tests (Gao et al ., ). Given the analytical problems observed in the hematology results reported by Awney et al .…”
Section: Analytical Problemsmentioning
confidence: 97%